2021
DOI: 10.1088/1748-9326/abf464
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale mapping of plant functional groups and plant traits in the High Arctic using field spectroscopy, UAV imagery and Sentinel-2A data

Abstract: The Arctic is warming twice as fast as the rest of the planet, leading to rapid changes in species composition and plant functional trait variation. Landscape-level maps of vegetation composition and trait distributions are required to expand spatially-limited plot studies, overcome sampling biases associated with the most accessible research areas, and create baselines from which to monitor environmental change. Unmanned aerial vehicles (UAVs) have emerged as a low-cost method to generate high-resolution imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 128 publications
2
47
0
Order By: Relevance
“…However, wavebands in NIR region (751-1075 nm) contributed the most (n = 313) in the discrimination in current study (Figure 9). These results agree with previous studies where leaf spectra have shown the greatest variation in the near-infrared and rededge regions [37,90,91]. Significant wavelengths in the red-edge region (680-750 nm) may be due to the variations in chlorophyll concentration, nitrogen concentration, and water content between different species [92,93].…”
Section: Discussionsupporting
confidence: 92%
“…However, wavebands in NIR region (751-1075 nm) contributed the most (n = 313) in the discrimination in current study (Figure 9). These results agree with previous studies where leaf spectra have shown the greatest variation in the near-infrared and rededge regions [37,90,91]. Significant wavelengths in the red-edge region (680-750 nm) may be due to the variations in chlorophyll concentration, nitrogen concentration, and water content between different species [92,93].…”
Section: Discussionsupporting
confidence: 92%
“…The overall high classification accuracy with macro-F1 values of over 80% for all three sites suggests that the classification performed well, comparable or better than other dronebased classifications in the high Arctic, such as Fraser et al [89] and Thomson et al [48]. We found no consistent bias in the misclassification of the ground-cover classes.…”
Section: Discussionsupporting
confidence: 71%
“…They can help transferring from local and detailed knowledge to broadscale environments with more spatial and temporal complexity and can improve the interpretation of satellite imagery [32]. In the Arctic, drones have been used for vegetation mapping [33][34][35], measurements of cryosphere characteristics [36][37][38][39][40][41][42][43][44][45], observations of permafrost thaw [46,47] and to help bridge the gap between field-and satellite-derived data [32,35,48]. Long-term monitoring is stated as a goal in many recently published drone studies (e.g., [49,50]), but as the technology is quite new, few current studies have compared results from drone data between years or even within the same season [32,35].…”
Section: Introductionmentioning
confidence: 99%
“…There are currently no civilian satellite programs capable of providing this type of data at the required spectral and spatial resolution, meaning that the imagery must be acquired from airborne sensors. Some studies have demonstrated that imagery collected from drone-based sensors can accurately map shrubland vegetation (Prošek and Šímová 2019) or predict functional traits in the arctic (Thomson et al 2021), but questions remain surrounding the capacity of these methods to differentiate small individuals in species-rich ecosystems (>20 species per 1 m 2 ), such as mixed woodland-grasslands. It may be possible, however, to generate a new nitrogen-index by selecting only bands common in multi-spectral sensors (Heim et al 2019) or correlate pre-existing multispectral remote sensing indices with the measured leaf %N values, eliminating the need for hyperspectral data collection and reducing the cost of both data acquisition and processing.…”
Section: Discussionmentioning
confidence: 99%